2013
DOI: 10.1179/1607845412y.0000000055
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and varicella zoster in children

Abstract: From 2005 to 2011, 25 children of both sexes (13 boys and 12 girls, mean age 7.8 ± 2.5 years, 5-12.4 years) with acute varicella zoster virus (VZV) infection were selected. Five patients showed venous thromboembolism characterized by deep venous thrombosis (DVT). Comparison of activated partial thromboplastin time, antithrombin III, D-dimer, lupus anticoagulant, free S protein (PS), C protein, and antiphospholipid and PS antibodies was performed on children with acute VZV and DVT (group I), acute uncomplicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…This could be due to the source of these infections which were mostly restricted to the nose and ear (in patients with mucormycosis and acute otitis media). The other reason might be the effect of infection in the induction of hypercoagulable state[1920] which may explain CVST in the patient with hepatitis B and the patient with a history of bacterial meningitis 1 month before thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the source of these infections which were mostly restricted to the nose and ear (in patients with mucormycosis and acute otitis media). The other reason might be the effect of infection in the induction of hypercoagulable state[1920] which may explain CVST in the patient with hepatitis B and the patient with a history of bacterial meningitis 1 month before thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, as in the literature, the autoantibodies appear to fully disappear within a few weeks, irrespective of the treatment used. Two studies have reported an asymptomatic decrease in the level of protein S in the context of infection by VZV, but without association to antibodies or thrombotic symptoms 27,28 . The prevalence of anti-protein S antibodies is not known, nor are the factors that can favor progression to this acute and severe form of thrombophilia, as chickenpox and HHV6 infections are extremely common and IPF the exception.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient protein S levels were low and anti phospholipids antibodies were positive. Ferrara M et al, (2013) reported five VZV cases with deep venous thrombosis (DVT) and concluded that acute VZV infection could be associated with coagulation disorders and production of inhibitory protein S antibodies [2]. Recently Januario G et al, reported a case of post varicella purpura fulminans with low protein S levels in a child [3].…”
Section: Case Presentationmentioning
confidence: 99%